2012 International Conference on Statistics in Science, Business and Engineering (ICSSBE) 2012
DOI: 10.1109/icssbe.2012.6396555
|View full text |Cite
|
Sign up to set email alerts
|

A study of occupational safety hazards: Safety and health issues in automotive industry

Abstract: This paper is based on a study on occupational safety hazards that affects the cost implication to the company with the existence of safety and health issues in Malaysian automotive industry. The aims of the study is to examine the extent of the occupational hazards in workplace resulting to the cost implication to the company by focusing on ergonomic, physical and chemical hazards. A set of comprehensive questionnaires was distributed to representative workers through self-administered method. The finding rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 4 publications
0
5
0
1
Order By: Relevance
“…The Organisational systems of multinational automotive industries have changed considerably and, as a result, complexity of products, workplaces and job operations increased (Michalos et al, 2010). Particularly, in the automotive manufacturing there are technological machines with high level of automation and human-machine interfaces (Hassam and Mahamad, 2012), Rezazadegan et al (2015) discussed the impact on the risk assessment. Kvarnstrom (1997) also observed that the implementation of high technological assembly lines resulted in more complicated manual operations.…”
Section: Introductionmentioning
confidence: 99%
“…The Organisational systems of multinational automotive industries have changed considerably and, as a result, complexity of products, workplaces and job operations increased (Michalos et al, 2010). Particularly, in the automotive manufacturing there are technological machines with high level of automation and human-machine interfaces (Hassam and Mahamad, 2012), Rezazadegan et al (2015) discussed the impact on the risk assessment. Kvarnstrom (1997) also observed that the implementation of high technological assembly lines resulted in more complicated manual operations.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, multivariate linear regression analysis in MS Excel and Minitab 7.1 statistical tools were used to establish the relation between overall productivity lost factor (OPLF) from accident index, lost time and severity index, and graphs plotted accordingly. The element of multivariate regression is expressed in equation [9]. Discussion Figure 1 shows that superficial wounds, burns injuries, and was prevailing among panel body work auto mechanics with an average of 28.1% and 18.7%.…”
Section: ( )mentioning
confidence: 96%
“…Furthermore, Table 3 shows the result of the multivariate liner regression model formulated to relate overall productivity lost factor with accident index, lost time and severity index as presented in equation (9). Table 3 indicates that the accident index has a beta coefficient ( ) of 659.2 at a probability value of 0.000 < 0.05.…”
Section: Analysesmentioning
confidence: 99%
“…Reemplazando, se tiene lo siguiente Por otro lado, autores como [25], clasifica los riesgos ocupacionales desde el punto de vista del origen y no del efecto, es decir, en riesgos: físicos, químicos, biológicos, carga física y psicosocial de inseguridad, del medio ambiente y, finalmente, de saneamiento ambiental. Otros autores [26], [27], [28], [29], [30], [31], los definen como riesgos ocupacionales.…”
Section: Caracterización De Peligros Y Riesgos En Las Empresas Del Seunclassified